Antenatal Corticosteroids and Preterm Neonatal Morbidity and Mortality among Women with and without Diabetes in Pregnancy - Battarbee, Ashley N.; Sandoval, Grecio; Grobman, William A.; Bailit, Jennifer L.; Reddy, Uma M.; Wapner, Ronald J.; Varner, Michael W.; Caritis, Steve N.; Prasad, Mona; Tita, Alan T.N.; Saade, George R.; Sorokin, Yoram; Rouse, Dwight J.; Tolosa, Jorge E.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2020)
Objective The objective of this study was to determine whether antenatal corticosteroid exposure has a differential association with preterm neonatal morbidity among women with and without diabetes.Study Design Secondary analysis of an observational cohort of 115,502 women and their neonates born in 25 U.S. hospitals (2008–2011). Women who delivered at 230/7 to 336/7 weeks' gestation and received antenatal corticosteroids were compared with those who did not receive antenatal corticosteroids. Women with a stillbirth and women who delivered a neonate that was not resuscitated were excluded. The primary outcome was neonatal respiratory distress syndrome or death within 48 hours. Secondary outcomes included composite neonatal morbidity (respiratory distress syndrome, necrotizing enterocolitis, grades 3–4 intraventricular hemorrhage, sepsis, or death) and mechanical ventilation. Multivariable modified Poisson regression was used to estimate the association between antenatal corticosteroid exposure and neonatal outcomes. Maternal diabetes (pregestational and gestational) was evaluated as a potential effect modifier, and sensitivity analyses were conducted to evaluate whether receipt of a partial, single, or multiple course(s) of antenatal corticosteroids influenced results.Results A total of 4,429 women with 5,259 neonates met inclusion criteria: 3,716 (83.9%) women received antenatal corticosteroids and 713 (16.1%) did not. Of the 510 diabetic women (181 pregestational and 329 gestational), 439 (86.1%) received antenatal corticosteroids. Of the 3,919 nondiabetic women, 3,277 (83.6%) received antenatal corticosteroids. Antenatal corticosteroid exposure was not associated with respiratory distress syndrome or early death (adjusted relative risk [aRR] = 0.94, 95% confidence interval [CI]: 0.85–1.04), composite neonatal morbidity (aRR = 0.98, 95% CI: 0.89–1.07), or mechanical ventilation (aRR = 0.95, 95% CI: 0.86–1.05). There was no significant effect modification of maternal diabetes on the relationship between antenatal corticosteroids and neonatal outcomes (p > 0.05), and outcomes were similar in sensitivity analyses of partial, single, or multiple courses of corticosteroids.Discussion Antenatal corticosteroid administered to reduce preterm neonatal morbidity does not appear to have a differential association among women with diabetes compared with those without.Key Points
Keywords: corticosteroids; diabetes; preterm birth; respiratory distress syndrome